La Mimesis como representación teatral en la Educación Inicial - Yancha Morales, Cynthia Maricela (2022)
This research is to elaborate playful workshops related to mimesis as a theatrical representation; for this purpose, the qualitative methodology was used because it analyzes the criteria of the teachers of Early Childhood Education parallel "B" employing the interview, diagnosing the knowledge and pedagogical praxis regarding mimesis and theatrical representation. Among the methods used are the bibliographic method, field, logical-inductive and non-experimental. The techniques used besides the interview were direct observation and the focus group that was applied to the parents. The results show that the educators do not have constant training on pedagogical strategies in which they can innovate with mimesis as theatrical representation. The educators are unaware of the benefits that theatrical representation brings to the children. In the same line, the most relevant conclusion details the design of the playful workshop. " Me activo y me divierto mientras imito " helps to develop significant learning in the children of Early Education of the "Naciones Unidas" Educational Unit, allowing them to have a helpful tool for pedagogical practice, with strategies of mastery in attention, retention, motivation and motor activation. These translate into the use of play, mime, singing, dance, comedy, poetry, and oral expression to encourage children's participation, improve school performance and behavior; in turn, work on socialization skills, self-esteem, neuorodidactics, creativity, imagination, motor, psychological and cognitive development.